2022
DOI: 10.3389/fmicb.2021.800938
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Outbreak of Carbapenemase-Producing Proteus mirabilis With Two Novel Salmonella Genomic Island 1 Variants Carrying Different blaNDM–1 Gene Copies in China

Abstract: NDM-1-producing multidrug-resistant Proteus mirabilis brings formidable clinical challenges. We report a nosocomial outbreak of carbapenem-resistant P. mirabilis in China. Six P. mirabilis strains collected in the same ward showed close phylogenetic relatedness, indicating clonal expansion. Illumina and MinION sequencing revealed that three isolates harbored a novel Salmonella genomic island 1 carrying a blaNDM–1 gene (SGI1-1NDM), while three other isolates showed elevated carbapenem resistance and carried a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, MDR genes coupled with multiple mobile gene elements were identified with two tandem copies of bla NDM-1 , which could confer an even broader spectrum of MDR capacity to the strain. Two tandem copies of bla NDM-1 have been reported from multiple species of bacterial chromosomes in previous reports [ 48 50 ], including P. mirabilis . Isolates with multiple copies of bla NDM-1 are known to show elevated carbapenem resistance [ 50 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, MDR genes coupled with multiple mobile gene elements were identified with two tandem copies of bla NDM-1 , which could confer an even broader spectrum of MDR capacity to the strain. Two tandem copies of bla NDM-1 have been reported from multiple species of bacterial chromosomes in previous reports [ 48 50 ], including P. mirabilis . Isolates with multiple copies of bla NDM-1 are known to show elevated carbapenem resistance [ 50 ].…”
Section: Discussionmentioning
confidence: 98%
“…Two tandem copies of bla NDM-1 have been reported from multiple species of bacterial chromosomes in previous reports [ 48 50 ], including P. mirabilis . Isolates with multiple copies of bla NDM-1 are known to show elevated carbapenem resistance [ 50 ]. In this study, 2 copies of bla NDM-1 were identified in P. mirabilis , yet one of them seems to have undergone a frame shift of the amino acid sequence.…”
Section: Discussionmentioning
confidence: 98%
“…[22][23][24] However, recent studies have demonstrated the existence of multiple copies of plasmid encoded bla NDM-1 . [25][26][27] These findings suggest a potential relationship between mobile elements and bla NDM gene duplication, as well as future research trends on the interaction between gene replication and host phenotypic.…”
Section: Introductionmentioning
confidence: 73%
“…8,81 Recently, multiple copies of bla NDM-1 -encoding plasmids have been reported with increasing frequency. [25][26][27][82][83][84] In those cases, diverse mechanisms mediated the generation of tandem repeat of bla NDM-1 gene by different IS elements, such as Tn3-like, 27 ISaba125 83 and ISCR1. 25,82 Importantly, there are different conclusions on whether repeat sequences affect the resistance phenotype in those strains.…”
Section: Discussionmentioning
confidence: 99%
“…Many mobile genetic elements, including plasmids, integrons, insertion sequences and transposons (Partridge et al, 2018), as well as SXT/R391 integrative conjugative elements (ICEs) and genomic islands (such as Salmonella/Proteus genomic islands, SGI/PGI), are found to mediate horizontal transfer of various antimicrobial resistance genes in P. mirabilis (Cummins et al, 2020;He et al, 2021). For example, the New Delhi metallo-βlactamase gene bla NDM-1 was sporadically found in P. mirabilis, and was located on plasmids (Bitar et al, 2020), PGI1 and SGI1 (Girlich et al, 2015;Yang et al, 2021). The multiresistance gene cfr that encodes an RNA methyltransferase conferring resistance to phenicols, lincosamides, oxazolidinones, pleuromutilins and streptogramin A (Shen et al, 2013), as well as the plasmidencoding RND efflux pump gene cluster tmexCD3-toprJ3 that reduces the sensitivity of multiple antimicrobials including tigecycline (Lv et al, 2020), were found to be located on SXT/ R391 ICEs (Wang et al, 2021b;Song et al, 2022).…”
Section: Introductionmentioning
confidence: 99%